Core‐Substituted Naphthalene Diimides: Influence of Substituent Conformation on Strong Visible Absorption. Issue 3 (23rd March 2017) - Quinn, Samuel; Davies, E. Stephen; Pfeiffer, Constance R.; Lewis, William; McMaster, Jonathan; Champness, Neil R.
Abstract: Functionalization of the aromatic core of naphthalene diimide (NDI) chromophores with morpholine substituents leads to molecules with strong absorbance in the visible spectrum. The shift of absorption maxima to lower energy is determined not only by the degree of substitution but also by the relative conformation and orientation of the tertiary amine with respect to the plane of the NDI. Abstract : "Plane" cooking : The strong absorbance of amine‐substituted naphthalene diimide (NDI) chromophores is determined by the relative orientation of the amine with respect to the aromatic core and not solely by the degree of substitution (see figure).